Kaolin micro powder, adhesive composition and preparation method and application thereof

By optimizing the raw material components and preparation technology of kaolin fine powder, the particle size and dispersion of kaolin fine powder are solved, and an adhesive with high whiteness, high gloss and excellent mechanical properties is achieved, which is suitable for paper products.

CN120554986APending Publication Date: 2025-08-29TONGXIANG LEISHI POWDER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510628474.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The particle size, whiteness and dispersion of existing kaolin fine powders are difficult to achieve the ideal state, resulting in uneven paper coating, reduced gloss and low mechanical properties.

Method used

By finely controlling the raw material components and preparation technology of kaolin fine powder, including selecting kaolin ratios of different whiteness (1:3:3~3:8:7), controlling the Al2O3 content, pH value, LOI and viscosity, combining crushing, grinding and homogenization treatment, kaolin fine powder with particle size less than 45μm and uniformity ≥98%, and the formulation with the adhesive composition is optimized.

Benefits of technology

It improves the whiteness, gloss, mechanical properties and chemical stability of the adhesive, ensures the uniformity and long-term stability of the coating process, and meets the quality requirements of high-end paper products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides kaolin micropowder, an adhesive composition as well as a preparation method and application of the adhesive composition. The kaolin micropowder comprises the following raw material components: first kaolin, second kaolin and third kaolin, wherein the weight ratio of the first kaolin to the second kaolin to the third kaolin is 1: 3: 3-3: 8: 7, the content of Al2O3 in the kaolin micro-powder is greater than 32%, the 325-mesh screen residue is less than or equal to 1.0%, the pH value of the kaolin micro-powder is less than or equal to 8.0, the LOI of the kaolin micro-powder is greater than or equal to 12%, and the viscosity of the kaolin micro-powder is greater than or equal to 1000Pa. S; the problems that in the prior art, due to the fact that the granularity, whiteness and dispersity of kaolin are difficult to reach ideal states, in the coating process of paper, a coating is not uniform, and glossiness is reduced are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a kaolin powder, an adhesive composition, and a preparation method and application thereof. Background Art

[0002] Kaolin, an important non-metallic mineral resource, plays a key role in multiple industrial sectors, particularly the paper industry, due to its excellent physical and chemical properties. In the papermaking process, kaolin, as a paper coating and filler, can significantly improve the smoothness, gloss, printability, and mechanical strength of paper. However, with the continuous advancement of modern papermaking technology, the performance requirements for kaolin are also increasing. In particular, coating-grade kaolin is required to have extremely high whiteness, good dispersibility and stability, as well as appropriate particle size and distribution to ensure the efficiency of the coating process and the stability of paper quality.

[0003] Currently, over 75% of high-quality refined kaolin is used globally in the papermaking industry. While domestic demand for kaolin is enormous, the supply of high-end coating-grade kaolin is relatively short, far from sufficient to meet the needs of the rapidly growing papermaking industry. This has prompted domestic research and production institutions to accelerate the development and research of kaolin in order to improve its quality and production.

[0004] Although some kaolin products already exist on the market, these products often have performance limitations. The preparation process for kaolin micropowder is generally traditional and lacks precise control, resulting in suboptimal particle size, whiteness, and dispersibility. This can lead to uneven coating and reduced gloss during the subsequent paper coating process. In actual production, the requirements for paper tubes vary due to the diverse uses of various paper products. Furthermore, the paper tube glue plays a crucial role in the paper tube's compressive strength, hardness, toughness, water resistance, heat resistance, and creep resistance. Summary of the Invention

[0005] The main purpose of the present invention is to provide a kaolin powder, an adhesive composition, a preparation method and application thereof, so as to solve the problems in the prior art that the particle size, whiteness and dispersibility of kaolin are difficult to reach the ideal state, thereby causing uneven coating, reduced gloss and low mechanical properties during the coating process of paper.

[0006] In order to achieve the above object, according to one aspect of the present invention, a kaolin powder is provided, which contains the following raw material components:

[0007] First kaolin, the whiteness of first kaolin is 75% to 80%;

[0008] Second kaolin, the whiteness of second kaolin is 85% to 90%;

[0009] The third kaolin has a whiteness of 80% to 90%;

[0010] Among them, the weight ratio of the first kaolin, the second kaolin and the third kaolin is 1:3:3 to 3:8:7, and the parameters of the kaolin fine powder are: Al2O3 content greater than 32%, 325 mesh sieve residue less than or equal to 1.0%, pH value less than or equal to 8.0, LOI greater than or equal to 12%, and viscosity greater than or equal to 1000 Pa.s.

[0011] Furthermore, the components of the first kaolin include, by weight percentage: SiO2 40% to 44%, Al2O3 35% to 39%, Fe2O3 0.5% to 0.6%, TiO2 0.5% to 1.5%, K2O ≤ 0.50%, Na2O ≤ 0.20%, SO3 ≤ 0.20%, water ≤ 1.0%, and the remainder is loss on ignition and trace elements. The COD value of the first kaolin is 8000ppm to 12000ppm. Preferably, the loss on ignition of the first kaolin is 5 to 15%.

[0012] Furthermore, in terms of weight percentage, the components of the second kaolin include: SiO2 42% to 46%, Al2O3 34% to 38%, Fe2O3 0.5% to 0.6%, TiO2 0.5% to 1.0%, K2O ≤ 0.50%, Na2O ≤ 0.20%, SO3 ≤ 0.20%, water ≤ 1.0%, and the balance is loss on ignition and trace elements. The COD value of the second kaolin is 3000ppm to 6000ppm. Preferably, the loss on ignition of the second kaolin is 5 to 10%.

[0013] Furthermore, in terms of weight percentage, the components of the third kaolin include: SiO2 44% to 48%, Al2O3 33% to 37%, Fe2O3 0.4% to 0.5%, TiO2 0.5% to 1.0%, K2O ≤ 0.40%, Na2O ≤ 0.20%, SO3 ≤ 0.20%, water ≤ 1.0%, and the balance is loss on ignition and trace elements. The COD value of the third kaolin is 500ppm to 2000ppm. Preferably, the loss on ignition of the third kaolin is 8 to 15%.

[0014] According to another aspect of the present invention, there is provided an adhesive composition, which comprises, in parts by weight:

[0015] 10-20 parts of polyvinyl alcohol;

[0016] 5-10 parts of polyurethane;

[0017] 5 to 10 parts of styrene-butadiene-styrene block copolymer;

[0018] 10-15 parts of kaolin powder;

[0019] 5-10 parts of talcum powder;

[0020] 3-5 parts of titanium oxide;

[0021] 5-10 parts of modified starch;

[0022] 0.5-5 parts of thickener;

[0023] 1 to 3 parts of a cross-linking agent;

[0024] 0.5-1 part of preservative;

[0025] 0.2-0.5 parts of pH regulator;

[0026] 0.5-1 part of surfactant;

[0027] 70-90 parts water;

[0028] The kaolin powder is any of the above kaolin powders.

[0029] Furthermore, the adhesive comprises, by weight:

[0030] 13-18 parts of polyvinyl alcohol;

[0031] 6-7 parts of polyurethane;

[0032] 5 to 9 parts of styrene-butadiene-styrene block copolymer;

[0033] 10-15 parts of kaolin powder;

[0034] 8-10 parts of talcum powder;

[0035] 3-4 parts of titanium oxide;

[0036] 8-9 parts of modified starch;

[0037] 2 to 4 parts thickener;

[0038] 1 to 3 parts of a cross-linking agent;

[0039] 0.5-0.9 parts of preservatives;

[0040] 0.2-0.5 parts of pH regulator;

[0041] 0.5-0.8 parts of surfactant;

[0042] 70-72 parts of water.

[0043] Furthermore, the thickener is one or more of hydroxypropyl methylcellulose, hydroxyethyl cellulose, carbomer, and xanthan gum.

[0044] Furthermore, the preservative is one or more of phenoxyethanol, methylisothiazolinone, and methylchloroisothiazolinone; and / or the pH adjuster is sodium acetate and / or ammonia water.

[0045] Furthermore, the surfactant is one or more of polyoxyethylene surfactants and alcohol polyether surfactants.

[0046] Furthermore, the crosslinking agent is one or more of melamine and polyhydroxy crosslinking agents.

[0047] According to another aspect of the present invention, there is also provided a method for preparing the adhesive composition as described above, comprising the following steps:

[0048] S1: adding 20 to 25 parts of water to polyvinyl alcohol and mixing to dissolve and disperse, and adding 10 to 15 parts of water to polyurethane and mixing to dissolve and disperse, respectively preparing a polyvinyl alcohol solution and a polyurethane solution, and mixing the two uniformly;

[0049] S2: mixing styrene-butadiene-styrene block copolymer with 10-15 parts of water to dissolve and disperse the copolymer, and adding the copolymer to the solution obtained in step S1, and mixing and stirring the mixture until uniform;

[0050] S3: Mix kaolin powder and talc with 15-20 parts of water to dissolve and disperse them, then add them to the solution obtained in step S2, and then add titanium oxide and mix and stir evenly;

[0051] S4: Mix the modified starch, cross-linking agent, and thickener with 10 to 15 parts of water for dispersion, add the mixture to the solution obtained in step S3, and then add the preservative and mix well;

[0052] S5: adding a pH regulator to the solution obtained in step S4 and adjusting the pH value to 4.5-6.5, then adding a surfactant and mixing and stirring uniformly, and then filtering to obtain an adhesive composition product.

[0053] According to another aspect of the present invention, there is also provided a use of the above adhesive composition in the field of paper product adhesives.

[0054] Provided herein is a method for preparing kaolin powder used in the present application, comprising the following steps:

[0055] S1: Crushing: crushing the first kaolin, the second kaolin, and the third kaolin into small pieces of gravel and coarse particles less than 3 cm in size;

[0056] S2: Grinding: Grinding the crushed stone and coarse particle powder into kaolin powder below 45μm through a vertical mill;

[0057] S3: Homogenization, using Roots blower technology to mix and homogenize the kaolin powder, so that the powder uniformity of the kaolin powder is ≥98%; the separator speed of the vertical mill is 1000-1600r / min, the main motor current is 20-25A, the fan current is 100-200, and the grinding roller pressure is 12-13.5kPa.

[0058] Using the technical solution of the present invention, the weight ratio of the first, second, and third kaolins is set at 1:3:3 to 2:5:3. This specific ratio optimizes the chemical and physical properties of the kaolin powder. Because different kaolin types have subtle differences in chemical composition, a reasonable ratio can be used to balance the contents of key components such as Al2O3 and SiO2, while controlling the concentrations of impurities such as Fe2O3 and TiO2, thereby ensuring the whiteness, purity, and stability of the kaolin powder.

[0059] The particle size of the crushed product is controlled to be below 3 cm. This size range is set based on the efficiency of the subsequent grinding process. Crushed products that are too large will increase grinding energy consumption, while those that are too small may cause unnecessary over-grinding during the grinding process, affecting the final particle size distribution of the micronized powder. Precise control of the crushing step provides raw materials of the appropriate size for subsequent grinding, ensuring efficient grinding and uniform product quality.

[0060] The particle size of the ground product is less than or equal to 45 μm, which is the ideal particle size range for kaolin powder use in adhesives. The smaller particle size helps improve the dispersion of the powder in the adhesive, reducing agglomeration. It also optimizes the rheological properties of the adhesive, making it more uniform and smooth during coating, which helps improve the surface smoothness and gloss of paper products.

[0061] The homogenization of kaolin powder reaches a uniformity of ≥98%. This ensures stable dispersion of the powder in the adhesive, preventing stratification and sedimentation, which is crucial for the long-term storage stability of the adhesive. The use of highly uniform kaolin powder in adhesives can improve the mechanical properties of paper products, such as tensile strength and flexural strength, while also ensuring the adhesive's optical properties, such as high whiteness, meeting the color and transparency requirements of paper products.

[0062] Kaolin powders have an Al2O3 content greater than 32% and a 325-mesh sieve residue of less than or equal to 1.0%. These performance indicators ensure that the kaolin powders have good chemical stability, low impurity content, and excellent dispersibility. The high Al2O3 content improves the powder's whiteness and optical properties, while the low 325-mesh sieve residue reduces the coarse particle content, further optimizing the powder's particle size distribution and enhancing its effectiveness in adhesives.

[0063] Precision processing of kaolin powder not only improves the quality of the powder itself but also significantly enhances the overall performance of adhesives, including whiteness, tensile strength, shear strength, and peel strength. This directly impacts the quality of paper products, improving their strength, smoothness, and gloss, meeting the stringent requirements for appearance quality and mechanical properties required of high-end paper products.

[0064] The technical solution of the present application achieves high-quality preparation of kaolin micropowder through raw material optimization and fine control of processing parameters. At the same time, when the prepared kaolin micropowder is applied to the adhesive formula provided in the present application, it shows significant application advantages in the paper products industry, with no stratification phenomenon and high whiteness. The adhesive composition formula provided in the present application also has excellent mechanical properties, and is particularly suitable for paper products, especially in the field of paper tube glue. DETAILED DESCRIPTION

[0065] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the embodiments.

[0066] As mentioned in the background technology, the technical purpose of this application is to provide a kaolin powder, an adhesive composition, and a preparation method and application thereof.

[0067] First, the present application provides a kaolin powder, which contains the following raw material components:

[0068] First kaolin, the whiteness of first kaolin is 75% to 80%;

[0069] Second kaolin, the whiteness of second kaolin is 85% to 90%;

[0070] The third kaolin has a whiteness of 80% to 90%;

[0071] Among them, the weight ratio of the first kaolin, the second kaolin and the third kaolin is 1:3:3 to 3:8:7, preferably, the weight ratio is 1:3:3 to 2:5:3, the Al2O3 content in the kaolin fine powder is greater than 32%, the 325 mesh sieve residue is less than or equal to 1.0%, the pH value of the kaolin fine powder is less than or equal to 8.0, the LOI (loss on ignition) of the kaolin fine powder is greater than or equal to 12%, and the viscosity of the kaolin fine powder is greater than or equal to 1000 Pa.s.

[0072] The presence of the first kaolin (whiteness 75% to 80%) provides a basic white background for the adhesive, ensuring the basic visual effect of the adhesive in the paper product.

[0073] The high whiteness of the second kaolin (whiteness 85% to 90%) and third kaolin (whiteness 80% to 90%) significantly improves the visual quality of the adhesive. By adjusting the mixing ratio (1:3:3 to 3:8:7), the optimal balance between cost and performance can be found, ensuring the adhesive has both high whiteness and controlled costs.

[0074] A high Al2O3 content not only enhances the whiteness of the kaolin powder, but more importantly, it increases the mechanical strength of the adhesive, improving the durability and stability of the bond. The higher the Al2O3 content, the harder the kaolin becomes, which helps enhance the hardness and abrasion resistance of paper products.

[0075] The fineness of the kaolin powder is controlled at a 325 mesh sieve residue of less than or equal to 1.0%, ensuring its uniform dispersion in the adhesive, avoiding stratification and precipitation caused by excessively large particles, and thereby improving the performance and storage stability of the adhesive.

[0076] A pH value less than or equal to 8.0 ensures good compatibility between kaolin powder and other chemical components in the adhesive, avoids chemical reactions caused by excessively high or low pH, and ensures stable performance of the adhesive during long-term use and storage.

[0077] LOI reflects the loss on ignition of kaolin at high temperatures, which primarily includes the loss of water and organic matter. A higher LOI indicates that the kaolin contains an appropriate amount of water and organic matter, which can act as a grinding aid or lubricant in the adhesive preparation process, helping to improve the flowability and dispersibility of the kaolin powder.

[0078] The high viscosity of kaolin powder ensures its stable presence in the adhesive, avoiding sedimentation and stratification during the coating process, which not only facilitates the uniform coating of the adhesive on the surface of paper products, but also improves the coating efficiency and the appearance quality of the finished product.

[0079] As can be seen from the above analysis, the kaolin powder formula of this application, by precisely controlling the whiteness, Al2O3 content, fineness, pH value, LOI, and viscosity of each kaolin, not only optimizes the visual effects of the adhesive, such as whiteness and gloss, but also significantly improves its mechanical properties, such as flexural strength, tensile strength, and abrasion resistance. Furthermore, this formula ensures the chemical stability, dispersion uniformity, and coating properties of the adhesive, enabling high performance and applicability in the paper product field, particularly in applications such as paper tubes.

[0080] In terms of the weight ratio selection of the three types of kaolin, by adjusting the ratio from 1:3:3 to 3:8:7, not only the whiteness and visual aesthetics of the adhesive are improved, but also a balance between cost-effectiveness and performance is ensured. Because in the preparation of kaolin micropowder, the cost of high-whiteness kaolin is often higher. By rationally mixing kaolins of different whiteness, the desired visual effects and mechanical properties can be achieved without significantly increasing costs.

[0081] Secondly, the present application also mentions a method for preparing kaolin powder, which includes obtaining a kaolin raw material, the kaolin raw material including a first kaolin, a second kaolin and a third kaolin; crushing the kaolin raw material to obtain a crushed product, the particle size of the crushed product is less than or equal to a first set value; grinding the crushed product to obtain a ground product, the particle size of the ground product is less than or equal to a second set value; homogenizing the ground product so that the uniformity of the ground product after homogenization is greater than or equal to a third set value; wherein the weight ratio of the first kaolin, the second kaolin and the third kaolin is 1: 3:3~3:8:7, the first setting value is 3 cm, the second setting value is 45um, the third setting value is 98%, the Al2O3 content in the kaolin micropowder is greater than 32%, the 325 mesh sieve residue is less than or equal to 1.0, the pH value of the kaolin micropowder is less than or equal to 8.0, the LOI is greater than or equal to 12%, the viscosity of the kaolin micropowder is greater than or equal to 1000 Pa.s, and the 24-hour sedimentation rate of the 33% solid content slurry of kaolin micropowder is less than 5%. Among them, uniformity refers to the dispersion consistency of the kaolin micropowder after mixing and homogenization, that is, the uniformity of the distribution of each component in the powder.

[0082] This application uses a fine crushing and grinding process to control the particle size of the kaolin raw material to less than 3 centimeters, and finally prepares kaolin micropowder with a particle size of less than 45μm, which greatly improves the rheological properties of the micropowder. The fine micropowder particles can significantly increase the viscosity of the adhesive. When the viscosity of the kaolin micropowder is greater than or equal to 1000Pa.s, the rheological properties of the adhesive are optimized, allowing it to maintain good uniformity and stability during the coating process. In addition, the fine-particle kaolin micropowder is easier to disperse evenly in the adhesive, reducing the stratification phenomenon caused by excessively large particles, thereby improving the overall performance of the final product.

[0083] Homogenization of kaolin powder ensures a uniformity of greater than or equal to 98%. This highly consistent kaolin powder is particularly important in adhesive formulations, as uniform powders bond more tightly with polymers like PVA, PU, ​​and SBS, forming a continuous interface and enhancing the adhesive's adhesion and mechanical strength. Uniform dispersion of kaolin powder also helps reduce air bubbles in the adhesive and improves the smoothness and gloss of the coating.

[0084] Kaolin powder has an Al2O3 content greater than 32% and a 325-mesh sieve residue of less than or equal to 1.0. This high-purity powder not only exhibits excellent whiteness but also significantly improves the optical properties of adhesives. Kaolin's high Al2O3 content and low sieve residue mean it contains fewer impurities and finer particles, providing a purer white background in adhesives, enhancing the reflectivity and visual quality of paper products.

[0085] Keeping the pH of kaolin powder below 8.0 helps maintain the chemical stability of the adhesive. A low pH reduces the possibility of reactions with acid-sensitive materials, ensuring that the adhesive's properties are not altered by chemical reactions during storage and use, thereby extending its shelf life. Furthermore, a stable pH helps maintain the adhesive's viscosity and dispersibility, preventing performance degradation due to pH fluctuations.

[0086] Setting the LOI value to 12% or greater reflects the high moisture and organic matter content of the kaolin powder. In the adhesive formulation, an appropriate amount of moisture and organic matter helps improve the powder's dispersibility and fluidity, making the adhesive easier to spread during application and enhancing efficiency. Although the kaolin powder's initial LOI value is high, the powder's uniform dispersion in the adhesive and the subsequent evaporation of moisture during the adhesive's drying process effectively control the LOI of the final product, thereby maintaining drying efficiency and long-term stability.

[0087] The 24-hour sedimentation rate of a 33% solids slurry of kaolin micropowder provided in this application is less than 5%, demonstrating the excellent suspension stability and anti-stratification capabilities of the kaolin micropowder. This is due to the fine particle size, low screen residue, and homogenization of the micropowder, which reduces frictional resistance between the micropowders. The use of additives such as surfactants further enhances the stability of the adhesive, allowing it to maintain fluidity and uniformity even at high solids content, facilitating coating operations and ensuring uniform coating thickness, thereby improving the mechanical properties and appearance quality of paper products.

[0088] In summary, the technical solution of the present application achieves the optimization of key parameters such as particle size, homogeneity, purity, pH value, LOI value and viscosity by strictly controlling the preparation process of kaolin micropowder, thereby significantly improving the application effect of the adhesive in paper products, including but not limited to improving mechanical strength, optimizing rheological properties, improving whiteness and gloss, controlling drying time and ensuring long-term stability.

[0089] Preferably, the components of the first kaolin include, by weight percentage, 40% to 44% SiO2; 35% to 39% Al2O3; 0.5% to 0.6% Fe2O3; 0.5% to 1.5% TiO2; 0% to 0.5% K2O; 0% to 0.2% Na2O; 0% to 0.2% SO3; 0% to 1.0% water; the remainder being loss on ignition and trace elements, wherein the COD value of the first kaolin is 8000ppm to 12000ppm.

[0090] The preferred kaolin component has an Al2O3 content of 35% to 39%, which helps improve the whiteness of the final kaolin powder. This increased aluminum oxide content reduces the impact of other colored impurities (such as Fe2O3), enhancing the powder's reflectivity and, in turn, improving the optical properties of the adhesive. The whiteness of kaolin powder is crucial to the appearance and printing quality of paper products, particularly in high-end paper and packaging materials, where high whiteness ensures excellent visual quality and printing compatibility.

[0091] By controlling the SiO2 content to 40% to 44%, and the contents of impurities such as K2O, Na2O, and SO3 to less than 0.5%, 0.2%, and 0.2%, respectively, the technical solution of this application effectively improves the purity of the kaolin micropowder and reduces the adverse effects on mechanical properties. As one of the main components of kaolin, the optimization of SiO2 content helps to provide a more stable micropowder structure, reduce friction between particles, and thus increase the bonding strength and bending resistance of the adhesive. The lower impurity content, especially the content of soluble salts such as potassium and sodium, reduces the shrinkage and deformation of the adhesive during the drying process, maintaining good dimensional stability.

[0092] This technical solution strictly controls the moisture content of kaolin powder, setting it between 0% and 1.0%. The appropriate amount of moisture helps improve the dispersibility of kaolin powder in adhesive formulations, thereby optimizing the adhesive's rheological properties and enabling more uniform and efficient coating during paper processing. Low moisture content reduces free water in the adhesive, avoiding excessive drying times and improving production efficiency, while also ensuring adhesive stability during storage and transportation.

[0093] Controlling the Fe2O3 and TiO2 contents to 0.5%-0.6% and 0.5%-1.5%, respectively, helps improve the durability and aging resistance of kaolin powder. Optimizing the content of Fe2O3 and TiO2, as colorants, reduces the risk of discoloration in the adhesive due to environmental factors. Furthermore, the photostability of TiO2 enhances the adhesive's durability under UV light, extending the lifespan of paper products. Controlling the Fe2O3 content also reduces oxidation during the drying process, maintaining long-term adhesive performance and appearance quality.

[0094] By controlling the loss on ignition (LOI) and the content of trace elements within the margin, the technical solution of the present application effectively ensures the chemical stability of the kaolin powder while improving the environmental performance of the adhesive. The loss on ignition reflects the content of volatile components such as organic matter in the kaolin powder. A higher loss on ignition may produce harmful gases during the drying process of the adhesive, affecting the working environment and the final quality of the paper product. Therefore, by controlling the loss on ignition, the decomposition reaction of the adhesive under high temperature conditions is reduced, ensuring the safety of production and use. At the same time, the control of trace elements avoids potential heavy metal pollution and enhances the environmental protection and market competitiveness of the adhesive.

[0095] In summary, the technical solution of the present application, by optimizing the chemical components of kaolin powder, not only improves its physical and chemical properties such as whiteness, purity, and light stability, but also enhances the comprehensive application performance of the adhesive, such as mechanical properties, rheological properties, durability, and environmental friendliness. These optimized properties have a significant effect on improving the processing efficiency, appearance quality, and service life of paper products, while also meeting the modern industry's pursuit of environmental protection, energy conservation, and high efficiency. Therefore, the kaolin powder and adhesive provided by the present invention can bring revolutionary technological progress to the paper products industry and become a high-quality choice in the market.

[0096] Preferably, the components of the second kaolin include, by weight percentage, 42% to 46% SiO2; 34% to 38% Al2O3; 0.5% to 0.6% Fe2O3; 0.5% to 1.0% TiO2; 0% to 0.5% K2O; 0% to 0.2% Na2O; 0% to 0.2% SO3; 0% to 1.0% water; the remainder is loss on ignition and trace elements, wherein the COD value of the second kaolin is 3000ppm to 6000ppm.

[0097] The preferred second kaolin content is 42% to 46% SiO2 and 34% to 38% Al2O3. This indicates that the kaolin micropowder has high contents of silicon and aluminum oxides, which contribute to improved optical properties of the adhesive, particularly whiteness. High SiO2 and Al2O3 contents form a dense, highly reflective coating, minimizing the effects of other impurities such as Fe2O3 and TiO2. Excessive levels of the latter can darken the micropowder or reduce its transparency, thereby affecting the visual quality of the final product. Controlling SiO2 and Al2O3 within specific ranges ensures optimal micropowder color and transparency, enhancing the aesthetics and print quality of paper products.

[0098] The Fe2O3 and TiO2 contents in the second kaolin micropowder are controlled between 0.5% and 0.6% and 0.5% and 1.0% respectively. Optimizing these contents helps reduce the negative effects of iron and titanium oxides on adhesive stability. As colorants, excessive Fe2O3 and TiO2 levels can cause color changes in the adhesive, affecting its application in paper products. Furthermore, Fe2O3 easily oxidizes in humid environments, and TiO2 has a certain photocatalytic effect. Properly controlling the amounts of these two enhances the adhesive's stability during storage and use, minimizing performance degradation due to oxidation or photocatalysis. Furthermore, lower Fe2O3 and TiO2 contents also help improve the adhesive's mechanical strength and reduce wear caused by hard particles in the coating.

[0099] Controlling the moisture content between 0% and 1.0% helps optimize the adhesive's rheological properties and drying efficiency. The appropriate amount of moisture improves the dispersion of kaolin powder in the adhesive, allowing for more uniform application during paper processing. However, excessive moisture content can prolong drying time, increase energy consumption, and reduce production efficiency. Keeping the moisture content low not only speeds up the adhesive's drying process and reduces energy consumption, but also ensures its stability during storage, preventing clumping and delamination caused by excess moisture.

[0100] Controlling the K2O, Na2O, and SO3 contents in the second kaolin fine powder to 0%-0.5%, 0%-0.2%, and 0%-0.2%, respectively, helps improve the chemical stability and environmental performance of the adhesive. The presence of soluble salts such as potassium, sodium, and sulfur oxides can affect the pH and ionic balance of the adhesive, leading to a decrease in chemical stability. Controlling the levels of these impurities reduces salting out during the drying process, avoiding damage to the coating of paper products. Furthermore, low levels of these impurities help reduce the adhesive's potential environmental pollution, particularly during waste paper recycling, by preventing the accumulation of heavy metals and hazardous substances and increasing the recycling value of paper products.

[0101] By controlling the loss on ignition (LOI) and trace element content, the preferred second kaolin powder can enhance the durability and aging resistance of the adhesive. LOI reflects the content of volatile components, such as organic matter, in the kaolin powder. Excessive LOI may generate harmful gases during adhesive drying and use, affecting the quality and safety of paper products. Controlling LOI reduces the decomposition of volatile organic compounds, maintaining the long-term stability of the adhesive and the health and safety of paper products. Furthermore, controlling trace element content, especially by avoiding heavy metal residues, not only improves the adhesive's environmental performance but also enhances its aging resistance, extending the lifespan of paper products.

[0102] Preferably, the components of the third kaolin include, by weight percentage, 44% to 48% SiO2; 33% to 37% Al2O3; 0.4% to 0.5% Fe2O3; 0.5% to 1.0% TiO2; 0% to 0.4% K2O; 0% to 0.2% Na2O; 0% to 0.2% SO3; 0% to 1.0% water; the remainder is loss on ignition and trace elements, wherein the COD value of the third kaolin is 500ppm to 2000ppm.

[0103] The preferred third-grade kaolin has a SiO2 content of 44%-48% and an Al2O3 content of 33%-37%. Optimizing the contents of these two components is directly related to the whiteness and gloss of the adhesive. SiO2 and Al2O3 are the main colorless components in kaolin. High levels of these components help improve the whiteness of the micropowder, which is particularly important in the paper product industry, as higher whiteness increases the reflectivity of the paper, enhancing visual quality and printing quality. Al2O3 also has excellent dispersibility and filling properties, forming a smooth, dense coating, thereby enhancing the gloss of the adhesive and making the surface of the paper product smoother and more beautiful.

[0104] Controlling the Fe2O3 content to 0.4% to 0.5% and the TiO2 content to 0.5% to 1.0% can reduce the coloring and hardening effects of the kaolin powder, thereby improving the mechanical properties of the adhesive. Fe2O3 and TiO2 are the key components that cause the color change and hardness increase of the powder. Moderate content helps maintain good adhesion and flexibility of the adhesive. Excessive Fe2O3 and TiO2 content will make the adhesive too hard, affecting its bonding effect and anti-bending properties in paper products. The preferred content range ensures that the adhesive maintains the necessary flexibility and ductility while providing sufficient strength.

[0105] Third, precise control of the moisture content in kaolin powder (0% to 1.0%) has a direct impact on the rheological properties and drying speed of the adhesive. The right amount of moisture can improve the dispersibility of kaolin powder in the adhesive, making the adhesive have better rheological properties, easier to apply, and able to form a uniform coating. However, too high a moisture content will prolong the drying time, increase energy consumption, and affect production efficiency. The preferred moisture content range ensures the fluidity of the adhesive during coating and rapid evaporation during the drying process, thereby speeding up the production rhythm of paper products.

[0106] The contents of K2O, Na2O, and SO3 are controlled at 0% to 0.4%, 0% to 0.2%, and 0% to 0.2%, respectively, which helps to improve the chemical stability of the adhesive and reduce its environmental impact. Potassium and sodium oxides are easily soluble in water and may interfere with the pH balance and conductivity of the adhesive, affecting its long-term stability. The presence of sulfate (SO3) may accelerate metal corrosion, leading to equipment damage and deterioration of adhesive performance. By strictly controlling the content of these impurities, not only is the potential chemical reaction reduced, maintaining the stability and service life of the adhesive, but the negative impact on the environment is also reduced, such as reducing the emission of heavy metal ions and harmful substances, and improving the recyclability and eco-friendliness of paper products.

[0107] The loss on ignition and the content of trace elements (such as heavy metals and organic residues) are controlled within a reasonable range in order to ensure the water resistance and anti-aging properties of the adhesive under different environmental conditions. The loss on ignition reflects the content of volatile components in kaolin, which may decompose during the drying or use of the adhesive, affecting its water resistance and bonding durability. The control of trace elements reduces the aging rate of the adhesive, especially avoids the reaction of metal ions with oxygen and moisture in the air to form oxides, which reduces the performance of the adhesive. The third kaolin powder at the preferred content can provide an adhesive with stronger moisture resistance and good viscosity under ultraviolet radiation and temperature and humidity changes, thereby extending the service life of paper products.

[0108] Preferably, in the preparation method of kaolin micropowder provided in the present application, the equipment used is a vertical mill when grinding the crushed product, the separator speed of the vertical mill during grinding is 1000-1600r / min, the current of the main motor of the vertical mill is 20-25A, the fan current of the vertical mill is 100-200A, and the grinding roller pressure of the vertical mill is 12-13.5kPa.

[0109] Optimal vertical mill grinding conditions, such as a separator speed of 1000-1600 rpm, a main motor current controlled at 20-25A, a fan current of 100-200A, and a roller pressure of 12-13.5 kPa, ensure that the kaolin micropowder particle size is below 45 μm while optimizing the micropowder morphology. The separator speed directly affects the micropowder classification process; a higher speed helps separate finer particles. Controlling the main motor and fan currents ensures stable operation of the vertical mill during the grinding process, avoiding uneven micropowder particle size due to current fluctuations. Adjusting the roller pressure effectively crushes coarse particles during the grinding process, while avoiding over-grinding and maintaining the micropowder's fine structure, which is beneficial to the adhesive's rheological properties and drying speed.

[0110] Under optimal grinding conditions, the vertical mill efficiently homogenizes the crushed product, resulting in a kaolin powder with a homogenization degree exceeding 98%. Controlling the separator speed allows for precise grading of powders of varying particle sizes, while adjusting the fan current facilitates suspension and uniform distribution of the powder. Furthermore, moderate roller pressure prevents powder agglomeration during the grinding process. This allows for more uniform dispersion of the kaolin powder with the other components in the subsequent adhesive preparation, improving the adhesive's viscosity and stability while avoiding stratification caused by powder agglomeration.

[0111] By optimizing the operating parameters of the vertical mill, the resulting kaolin powder significantly enhances the mechanical properties of adhesives. Fine and uniform kaolin powder provides enhanced filling in adhesives, forming a continuous and dense interface layer, improving the adhesive's cohesion and adhesion to the substrate. Furthermore, the uniform powder reduces bubbles and defects in the adhesive, optimizing its uniformity and leveling properties, thereby forming a stronger adhesive layer within the paper product and enhancing its tensile and flexural resistance.

[0112] The optimized grinding conditions of the vertical mill minimize impurities in the powder and maintain the high whiteness of the kaolin powder. The fine and uniform powder particles help increase the adhesive's refractive index, reduce light scattering, and thus enhance its gloss. When applied to paper products, adhesives with high whiteness and gloss not only maintain the paper's original visual appearance but also enhance its surface smoothness and reflectivity, improving both the aesthetics and print quality of the paper.

[0113] Optimized vertical mill grinding conditions produce kaolin powder with an appropriate viscosity (≥1000 mPa.s), which facilitates control of the adhesive's viscosity, ensuring smooth flow during application without drying out too quickly. The fine kaolin powder reduces internal friction and improves fluidity, while the higher viscosity ensures uniform application and film-forming properties on the paper product surface. Furthermore, the fineness and homogeneity of the powder facilitate uniform moisture evaporation during the drying process, accelerating drying and improving production efficiency.

[0114] Precise control of the vertical mill during the grinding process can reduce the moisture and organic matter content in the powder, which directly benefits the chemical stability and long-term storage of the adhesive. Low moisture content reduces the opportunity for microbial growth during storage, preventing deterioration and aging. Controlling the organic matter content ensures that the adhesive is less susceptible to chemical reactions under high temperatures or sunlight, maintaining its stability in various environments, extending its shelf life, and reducing production costs.

[0115] Preferably, the equipment for homogenizing the ground product in the present application is a Roots blower.

[0116] The Roots blower technology is used to homogenize the ground products, so that the uniformity of the ground products reaches more than 98%. This technology effectively improves the stability and performance consistency of the micropowder in the adhesive, reduces stratification and precipitation, and especially during the slurry preparation and coating process, the highly uniform kaolin micropowder can form a more stable system with other components, thereby enhancing the bonding force between the layers.

[0117] The present application also provides an adhesive composition, which includes the following components in parts by weight: 10 to 20 parts of polyvinyl alcohol; 5 to 10 parts of polyurethane; 5 to 10 parts of styrene-butadiene-styrene block copolymer; 10 to 15 parts of kaolin powder; 5 to 10 parts of talc; 3 to 5 parts of titanium oxide; 5 to 10 parts of modified starch; 0.5 to 5 parts of thickener; 1 to 3 parts of cross-linking agent; 0.5 to 1 part of preservative; 0.2 to 0.5 parts of pH adjuster; 0.5 to 1 part of surfactant; and 70 to 90 parts of water; wherein the kaolin powder is the kaolin powder in the above-mentioned Example 3, and the water in the examples of the present application is all deionized water.

[0118] The combination of polyvinyl alcohol (PVA), polyurethane (PU), and styrene-butadiene-styrene block copolymer (SBS) ensures the adhesive possesses excellent mechanical properties. PVA provides initial tack, the elasticity and adhesion of SBS complement the deficiencies of PVA, and PU contributes high strength and durability. The three work synergistically to effectively enhance the tensile and shear strength of the adhesive. This is verified in the test data of Examples 4 to 13, which show that both tensile and shear strengths are superior to those of the comparative example.

[0119] The addition of kaolin powder not only improves the adhesive's physical properties but also significantly enhances its adhesion to paper, thereby increasing peel strength. The use of modified starch further enhances the adhesive's bonding strength, ensuring that the bond maintains high integrity and durability even when subjected to external forces during paper processing.

[0120] The kaolin powder prepared in this application has high whiteness, and the addition of talc and titanium oxide effectively improves the whiteness of the adhesive.

[0121] The mesh size of kaolin powder is controlled within a reasonable range, and the use of surfactants achieves good dispersion of adhesive components, avoids stratification and precipitation, and ensures the uniformity and stability of the adhesive during long-term storage and application.

[0122] The addition of preservatives and pH adjusters effectively extends the shelf life of the adhesive. Preservatives inhibit microbial growth, while pH adjusters maintain a suitable acid-base environment for the adhesive. These two factors, combined with the inherent stability of kaolin powder, ensure the long-term stability of the adhesive under storage conditions, allowing it to maintain its bonding properties over an extended period of time.

[0123] By precisely controlling the amount of thickener, the adhesive achieves the ideal viscosity, ensuring easy application without excessive viscosity, thus ensuring good performance and coating efficiency. Furthermore, the use of a crosslinker accelerates the adhesive's curing process and shortens drying time, which is crucial for increasing paper product production speeds, particularly when rapid, continuous operation is required on the production line, significantly improving efficiency and capacity.

[0124] The adhesive's water resistance is due to the crosslinker, which creates a more stable network structure after curing, enhancing its bonding ability and durability in humid environments. The combination of polyurethane and SBS further strengthens this characteristic, allowing the adhesive to maintain high bonding performance even in high humidity environments.

[0125] Preferably, the adhesive includes, by weight, 13 to 18 parts of polyvinyl alcohol; 6 to 7 parts of polyurethane; 5 to 9 parts of styrene-butadiene-styrene block copolymer; 10 to 15 parts of kaolin powder; 8 to 10 parts of talc; 3 to 4 parts of titanium oxide; 8 to 9 parts of modified starch; 2 to 4 parts of a thickener; 1 to 3 parts of a cross-linking agent; 0.5 to 0.9 parts of a preservative; 0.2 to 0.5 parts of a pH regulator; 0.5 to 0.8 parts of a surfactant; and 70 to 72 parts of water.

[0126] Specifically, in combination with the data in Table 4 (specifically, Example 6, Example 11 and Example 10), when the proportion of each component in the adhesive is within the above range, it can ensure that the tensile strength of the formed product is within a higher range, that is, 4.9 MPa-5.1 MPa, while the tensile strength in the remaining embodiments is below 4.9 MPa, and the shear strength is within the range of 4.0 MPa-4.2 MPa, the peel strength is within the range of 16 N / 25 mm-18 N / 25 mm, the whiteness is within the range of 86%-87%, the storage stability is 6 months, the viscosity is 2600 mPa.s-2800 mPa.s, the drying time is 5 min, and the water resistance is 13 h-14 h. Compared with the components of the adhesive in the above embodiments, all performances are greatly improved.

[0127] Preferably, the thickener is one or more of hydroxypropyl methylcellulose (HPMC), hydroxyethyl cellulose (HEC), carbomer, and xanthan gum.

[0128] Using hydroxypropyl methylcellulose (HPMC), hydroxyethyl cellulose (HEC), carbomer, and xanthan gum as thickeners can significantly improve the rheological properties of adhesives. These thickeners primarily increase the viscosity of the adhesive, optimizing its rheological properties and enabling it to form a more uniform film during coating. HPMC and HEC, as natural polymer thickeners, can form a three-dimensional network structure through intermolecular hydrogen bonds, effectively increasing the viscosity of the adhesive while maintaining good thixotropy. This means that the adhesive maintains a high viscosity when stationary, but rapidly decreases under shear forces, facilitating coating and improving production efficiency.

[0129] The addition of thickeners helps promote uniform dispersion of adhesive components. Cellulose derivatives such as HPMC and HEC have excellent dispersing capabilities, preventing the precipitation of solid particles such as kaolin powder and talc in adhesives, thereby maintaining adhesive stability. Carbomer and chloroprene gum also prevent particle agglomeration through the charge distribution within their molecular structures, ensuring that the adhesive components remain evenly distributed over time, avoiding potential stratification or precipitation during storage and use.

[0130] Thickeners such as HPMC and HEC not only increase the viscosity of adhesives but also help improve their film-forming properties. During the drying process, these thickeners promote the formation of a continuous, dense film layer, enhancing its adhesion and tensile strength. This enhanced film-forming property is particularly important for paper processing, ensuring a smooth, non-flaking surface coating after adhesive treatment, improving the durability and aesthetics of the paper.

[0131] Using carbomer or xanthocyanidin as a thickener can significantly enhance the adhesive's anti-settling properties. Carbomer and xanthocyanidin form a stable gel structure within the adhesive that effectively resists the settling of solid particles under gravity. Even after prolonged standing, the adhesive maintains its uniform composition, avoiding viscosity changes and stratification caused by settling. This extends the adhesive's operability and improves processing flexibility and reliability.

[0132] Thickeners can also control the coating thickness and adjust the viscosity of adhesives. HPMC and HEC adjust viscosity, making it easier to control film thickness during the coating process, avoiding uneven coating due to too low viscosity or coating difficulties caused by too high viscosity. Carbomer and chloroform gum can adjust the viscoelasticity of the adhesive as needed, achieving the desired coating thickness at varying coating speeds and pressures, optimizing paper product processing and reducing production waste.

[0133] Thickeners can improve the storage stability of adhesives. The addition of HPMC, HEC, carbomer, and xanthan gum enhances the adhesive's internal structural stability, reducing performance degradation caused by temperature fluctuations or prolonged storage. These thickeners form a stable network structure, maintaining the chemical balance of the adhesive components. Even under harsh storage conditions, the adhesive maintains excellent performance, reduces scrap due to deterioration, and reduces production costs.

[0134] Preferably, the preservative is one or more of phenoxyethanol, methylisothiazolinone, and methylchloroisothiazolinone.

[0135] Preferred preservatives such as phenoxyethanol, methylisothiazolinone (MIT), and methylchloroisothiazolinone (CMIT) can enhance the microbial stability of adhesives. These preservatives protect adhesives from bacteria, mold, and other microorganisms by disrupting or inhibiting microbial cell membranes, preventing their growth and reproduction. Phenoxyethanol has broad-spectrum antimicrobial activity and is not easily metabolized by microorganisms; MIT and CMIT are known for their potent bactericidal effects. The addition of these preservatives maintains the long-term stability of the adhesive, especially under warm and humid storage conditions, significantly reducing the risk of microbial deterioration and extending its shelf life.

[0136] In addition to their bactericidal properties, preservatives can also indirectly reduce adhesive delamination and sedimentation. Microbial activity can cause changes in the adhesive's internal composition, accelerating delamination and sedimentation. The addition of phenoxyethanol, MIT, and CMIT inhibits microbial growth while maintaining the adhesive's chemical balance. This reduces colloidal system instability caused by microbial metabolites, thereby preventing physical property degradation during storage and transportation.

[0137] Using optimal preservatives can maintain the hygiene, safety, and quality of paper products. Adhesives are widely used in paper product manufacturing, such as in cardboard bonding and paper tube manufacturing. If active microorganisms are present in adhesives, they can cause stains, mold, or even corrosion on the surface of paper products, affecting their appearance and functionality.

[0138] Phenoxyethanol, MIT, and CMIT, as preservatives, not only effectively kill bacteria but also enhance the adhesive's overall performance and safety due to their excellent chemical stability and minimal irritation to humans. While maintaining the adhesive's original properties, the addition of these preservatives prevents performance degradation caused by microbial activity, such as changes in viscosity and pH fluctuations, while also reducing irritation to human skin and the respiratory system.

[0139] Choosing phenoxyethanol, MIT, and CMIT as preservatives optimizes adhesive storage conditions and extends shelf life without significantly increasing costs. These preservatives are relatively low-cost yet highly effective, ensuring adhesive stability across a wide range of temperature and humidity conditions. By eliminating specialized requirements during adhesive storage and transportation, overall logistics costs are reduced, while also minimizing waste generated by premature failure, resulting in cost savings and efficient resource utilization.

[0140] Preferably, the pH regulator is sodium acetate and / or aqueous ammonia.

[0141] Sodium acetate and / or ammonia water are preferably used as pH regulators, which can accurately adjust the pH value of the adhesive to the ideal range of 4.5-6.5. The pH value within this range is conducive to the stable presence of various polymer components in the adhesive, especially polymers such as polyvinyl alcohol (PVA), polyurethane (PU) and styrene-butadiene-styrene block copolymer (SBS). They show better stability in a slightly acidic to neutral environment, avoiding molecular degradation or coagulation caused by excessively high or low pH, and ensuring the long-term storage and performance of the adhesive. At the same time, the use of sodium acetate and ammonia water not only controls the pH value of the adhesive, but also optimizes its bonding properties. The bonding efficiency of the polymer is closely related to the pH value of the medium in which it is located. With the help of the pH regulator, the adhesive is maintained in an environment that is conducive to the formation of hydrogen bonds between the polymer chains, which strengthens the cohesion of the adhesive and improves its adhesion to paper. At the same time, precise adjustment of the pH value helps to disperse fillers such as kaolin powder and talc, avoiding agglomeration caused by the charge effect, thereby achieving uniform paper coating and improving the quality and aesthetics of paper products.

[0142] Preferably, the surfactant is one or more of polyoxyethylene (PEG) surfactants and alcohol polyether surfactants.

[0143] Polyoxyethylene (PEG) surfactants and alcohol polyether surfactants are preferred because they significantly improve the wettability and dispersibility of adhesives. These surfactants reduce the surface tension between water and other non-aqueous phase components, making it easier for the adhesive to form a continuous wetting layer on the paper surface, improving coating quality. Furthermore, surfactants can coat micropowder particles, such as kaolin and talc, reducing interparticle friction, preventing agglomeration, and promoting uniform dispersion in the adhesive, thereby enhancing the uniformity and stability of the adhesive.

[0144] The use of polyoxyethylene (PEG) surfactants and alcohol polyether surfactants can optimize the rheological properties of adhesives. These surfactants form a hydrophilic-hydrophobic balance within the adhesive, regulating the adhesive's viscosity and plasticity, resulting in good leveling and self-healing properties during coating. This optimized rheological property ensures adhesive stability and consistency at varying coating speeds and pressures, improving production efficiency and product quality.

[0145] The addition of surfactants improves the interfacial tension between the adhesive and paper, promoting good adhesion between the two. They can penetrate the gaps between paper fibers, pre-wetting and pre-treating the paper surface, making it easier for the adhesive to spread on the paper and forming a tight bond.

[0146] Polyoxyethylene (PEG) and alcohol polyether surfactants are chemically stable and less susceptible to environmental factors such as humidity and temperature fluctuations, thus helping to improve the corrosion resistance of adhesives. Surfactants form a protective film on the adhesive surface, reducing external environmental erosion of the adhesive's internal chemical structure and extending the adhesive's service life, especially in applications where paper products are exposed to moisture or salt spray.

[0147] Polyoxyethylene (PEG) surfactants and alcohol polyether surfactants also have a certain antistatic effect. They can form a thin conductive layer on the adhesive surface, reducing the accumulation of static charge, thereby avoiding the degradation of adhesive performance and production safety hazards caused by electrostatic discharge. Antistatic properties are particularly critical during high-speed coating and winding processes, preventing adsorption between sheets or between sheets and machine surfaces, thereby improving the processing efficiency and safety of paper products.

[0148] Preferably, the crosslinking agent is one or more of melamine and polyhydroxy crosslinking agents.

[0149] Melamine and polyhydroxy crosslinkers are preferred as crosslinkers, which can significantly enhance the cohesion and mechanical strength of the adhesive. The crosslinker forms a three-dimensional network structure by chemically reacting with the polymer chains in the adhesive matrix. Melamine, as a crosslinker, can form stable crosslinking points with polymers such as polyvinyl alcohol (PVA), increasing intermolecular interactions, thereby improving the hardness and heat resistance of the adhesive. The polyhydroxy crosslinker, through its polyhydroxy functional groups, reacts with the hydroxyl groups of the polymer, enhancing intermolecular hydrogen bonding, further improving the tensile strength and shear resistance of the adhesive.

[0150] The addition of crosslinkers, particularly melamine and polyol crosslinkers, can effectively improve the adhesive's water resistance. The crosslinking reaction creates a tighter structure within the adhesive, reducing the pathways for water penetration and thereby enhancing its adhesion and stability in humid environments. The urea-formaldehyde resin formed after melamine crosslinking exhibits excellent water insolubility and hydrolysis resistance, effectively preventing water intrusion and maintaining the adhesive's bonding properties.

[0151] Preferred crosslinking agents (such as melamine and polyhydroxy crosslinking agents) can optimize the aging resistance of adhesives. By forming a stable chemical crosslinking network, the crosslinking agent reduces the molecular breakage of the adhesive under the action of ultraviolet rays, oxidation and thermal stress, and improves its stability during long-term use. The urea-formaldehyde resin formed by melamine crosslinking has good thermal stability and chemical resistance, can resist the performance degradation caused by environmental factors, and maintain the bonding strength and mechanical properties of the adhesive. The polyhydroxy crosslinking agent increases the ability of the adhesive to resist erosion by the external environment through its stable crosslinking structure.

[0152] The addition of a crosslinker also enhances the adhesive's penetration and adhesion to paper. The crosslinking reaction allows the adhesive molecules to form a stronger bond between paper fibers, improving interfacial adhesion. Melamine and polyhydroxy crosslinkers react with the hydroxyl groups in paper fibers, forming a stronger bond on the paper surface. This maintains a strong bond even when the paper is bent or folded, preventing the adhesive layer from peeling and improving the durability and appearance of the paper product.

[0153] The present application also provides a method for preparing an adhesive, comprising the following steps:

[0154] S1: adding 20 to 25 parts of water to polyvinyl alcohol and mixing to dissolve and disperse, and adding 10 to 15 parts of water to polyurethane and mixing to dissolve and disperse, respectively preparing a polyvinyl alcohol solution and a polyurethane solution, and mixing the two uniformly;

[0155] S2: mixing styrene-butadiene-styrene block copolymer with 10-15 parts of water to dissolve and disperse the copolymer, and adding the copolymer to the solution obtained in step S1, and mixing and stirring the mixture until uniform;

[0156] S3: Mix kaolin powder and talc with 15-20 parts of water to dissolve and disperse them, then add them to the solution obtained in step S2, and then add titanium oxide and mix and stir evenly;

[0157] S4: Mix the modified starch, cross-linking agent, and thickener with 10 to 15 parts of water for dispersion, add the mixture to the solution obtained in step S3, and then add the preservative and mix well;

[0158] S5: adding a pH regulator to the solution obtained in step S4 and adjusting the pH value to 4.5-6.5, then adding a surfactant and mixing and stirring uniformly, and then filtering to obtain an adhesive composition product.

[0159] Specifically, the dissolution temperature in step S1 is maintained at 80°C to 90°C. This temperature range is ideal for the dissolution of PVA, which can ensure that the PVA molecular chains are fully stretched to form a stable polymer network structure, providing the adhesive with good bonding performance and initial adhesion. At the same time, by stirring the polyvinyl alcohol and polyurethane components to mix evenly, the comprehensive performance of the adhesive is enhanced, including improving crack resistance, flexibility and adhesion to paper-based materials.

[0160] The addition of styrene-butadiene-styrene block copolymer (SBS) in step S2 not only provides the properties of an elastomer and enhances the bonding strength and toughness of the adhesive, but also can penetrate into the micropores of the paper fibers to form a tight bonding layer, which has a significant effect on improving the shear strength and tensile strength of the paper product.

[0161] The fine particle size and high purity of the kaolin powder in step S3 enable it to be evenly distributed in the adhesive, enhancing the smoothness and glossiness of the coating and improving the surface quality of the paper product; the addition of talcum powder optimizes the fluidity of the adhesive, and the addition of titanium oxide further enhances the whiteness and hiding power of the adhesive, making the appearance of the paper product more beautiful.

[0162] The modified starch in step S4 can improve the film-forming properties of the adhesive and increase its adhesion to paper fibers, while the cross-linking agent promotes the cross-linking of the adhesive during the drying process, thereby improving the mechanical strength and water resistance of the final product.

[0163] The acidic range in step S5 helps to improve the stability and anti-corrosion performance of the adhesive. At the same time, the addition of the surfactant improves the wettability and dispersibility of the adhesive, ensures the uniform distribution of all components in the adhesive, reduces stratification and precipitation, and improves the storage stability and use effect of the adhesive.

[0164] The adhesive produced by the above-described preparation method exhibits excellent viscosity, tensile strength, shear strength, peel strength, and whiteness, while maintaining good storage stability, drying quickly, and exhibiting excellent water resistance. These optimized properties, particularly in adhesives for paper products, can provide a more stable and long-lasting adhesive effect, improving the bonding performance of structures such as thin cardboard and paper tubes, and enhancing the mechanical strength of paper products, such as tensile strength and bending resistance, thereby preventing damage caused by external forces.

[0165] The following Examples 1-3 are examples of kaolin micropowder formulas provided in this application. The preparation methods adopted in Examples 1-3 are as follows: when grinding the crushed product, the equipment used is a vertical mill, and the separator speed of the vertical mill during grinding is 1000-1600 r / min, the current of the main motor of the vertical mill is 20-25 A, the fan current of the vertical mill is 100-200 A, and the grinding roller pressure of the vertical mill is 12-13.5 kPa; Examples 4-13 are examples of adhesives prepared using kaolin micropowder.

[0166] Example 1

[0167] In this embodiment, the weight ratio of the first kaolin, the second kaolin, and the third kaolin is 1:3:3. The specific components are shown in Table 1 below:

[0168] Table 1: Example 1 Kaolin powder formulation

[0169] First Kaolin Second Kaolin Third kaolin Ratio 14% 43% 43% <![CDATA[SiO2]]> 42 44 46 <![CDATA[Al2O3]]> 37 36 34 <![CDATA[Fe2O3]]> 0.6 0.5 0.5 <![CDATA[TiO2]]> 1 0.8 0.6 <![CDATA[K2O]]> 0.5 0.4 0.3 <![CDATA[Na2O]]> 0.2 0.1 0.1 <![CDATA[SO3]]> 0.2 0.1 0.1 water 1 0.8 0.5 Loss on ignition 12 8 10 Whiteness 78 88 88 COD 10000 5000 2000

[0170] Example 2

[0171] In this embodiment, the weight ratio of the first kaolin, the second kaolin, and the third kaolin is 2:5:3. The specific components are shown in Table 2 below:

[0172] Table 2: Example 2 Kaolin powder formulation

[0173]

[0174]

[0175] Example 3

[0176] In this embodiment, the weight ratio of the first kaolin, the second kaolin, and the third kaolin is 3:8:7. The specific components are shown in Table 3 below:

[0177] Table 3: Example 3 Kaolin powder formulation

[0178]

[0179]

[0180] Example 4

[0181] The present application provides an adhesive composition, which comprises, in parts by weight:

[0182] 12 parts of polyvinyl alcohol;

[0183] 6 parts of polyurethane;

[0184] 6 parts of styrene-butadiene-styrene block copolymer;

[0185] 12 parts of kaolin powder;

[0186] 7 parts of talcum powder;

[0187] 4 parts of titanium oxide;

[0188] 6 parts of modified starch;

[0189] 2 parts thickener;

[0190] 2 parts of cross-linking agent;

[0191] 0.8 parts of preservatives;

[0192] 0.3 parts of pH adjuster;

[0193] 0.8 parts of surfactant;

[0194] 85 parts water;

[0195] Wherein, the kaolin powder is the kaolin powder prepared in Example 2.

[0196] The present application provides an adhesive composition, which comprises the following steps by weight:

[0197] S1: Add polyvinyl alcohol and polyurethane to 20 parts of water and 15 parts of water respectively, mix and dissolve them.

[0198] Producing polyvinyl alcohol solution and polyurethane solution;

[0199] S2: Mix styrene-butadiene-styrene block copolymer with 15 parts of water to dissolve and disperse, and add to step

[0200] The solution obtained in step S1 was mixed and stirred uniformly;

[0201] S3: Mix kaolin powder and talc with 25 parts of water, dissolve and disperse them, and then add them to the mixture obtained in step S2.

[0202] Then add titanium oxide to the solution and mix well;

[0203] S4: Mix the modified starch, cross-linking agent, thickener and 10 parts of water and disperse them, then add them to the mixture prepared in step S3.

[0204] Then add the preservative to the obtained solution and mix well;

[0205] S5: adding a pH regulator to the solution obtained in step S4 and adjusting the pH value to 4.5-6.5, then adding a surfactant and mixing and stirring uniformly, and then filtering to obtain an adhesive composition product.

[0206] Examples 5-13

[0207] Examples 5-13 are basically the same as Example 4, except that the raw material ratios are different, as shown in Table 4:

[0208] Table 4: Formulations of adhesive compositions of Examples 4 to 13

[0209]

[0210]

[0211] Table 4 (Continued) Adhesive Formulations for Examples 4-13 and Comparative Examples 1-2

[0212]

[0213]

[0214]

[0215] Comparative example of kaolin powder

[0216] Comparative Example 1

[0217] The similarities between the raw material ratios and preparation methods of Comparative Example 1 and Examples 4-13 are not repeated here. The difference is that the kaolin powder of Comparative Example 1 uses ordinary kaolin on the market, and the Al2O3 content in the ordinary kaolin is greater than 28%, the LOI content is greater than 15%, the 325 mesh (%) is less than 1.0, the pH value is less than or equal to 8.0, the viscosity is greater than or equal to 900 mPa.s, and the whiteness is less than or equal to 80%.

[0218] Adhesive Comparison

[0219] Comparative Example 2 and Comparative Example 3

[0220] The similarities between Comparative Examples 2 and 3 and Examples 4-13 are not repeated here. The difference is that the mass fractions of polyvinyl alcohol, polyurethane, styrene-butadiene-styrene block copolymer, and kaolin powder are not within the numerical range provided in this application. Please see Table 4 for details.

[0221] The manufacturers and models of the raw materials in Examples 4 to 13 and Comparative Examples 1 to 3 are as follows:

[0222] The manufacturer of polyvinyl alcohol is Japan Kuraray, and its model is PVOH-124;

[0223] The polyurethane manufacturer is BASF, and its model is AS-626SH;

[0224] The manufacturer of styrene-butadiene-styrene block copolymer is Li Changrong Chemical, and its model is SBS 3566;

[0225] The manufacturer of talc powder is IMIFABI, model number is HTP2L;

[0226] The manufacturer of titanium oxide is Chemours, model number is Ti-Pure TS-6300;

[0227] The manufacturer of hydroxypropyl methylcellulose is Dow Chemical, and the product model is WALOCEL TM MKX 45000PF40 L;

[0228] The manufacturer of hydroxyethyl cellulose is Dow Chemical, and the product model is Cellosize TM QP-4400H;

[0229] The manufacturer of Carbomer is Wanhua Chemical, and the product model is WH-Carbomer 940;

[0230] The manufacturer of Huangbo glue is Ordos Zhongxuan Biochemical Co., Ltd., and the product model is F80;

[0231] The manufacturer of melamine is Mitsui Chemicals, and the product model is Sumika Melamine;

[0232] The manufacturer of trimethylolpropane triether is Wanhua Chemical, and the product model is WH-TMPTA;

[0233] The manufacturer of phenoxyethanol is Dow Chemical, and the product model is Phenoxyethanol;

[0234] The manufacturer of methylisothiazolinone is Dow Chemical, and the product model is CG;

[0235] The manufacturer of methylchloroisothiazolinone is Dow Chemical, and the product model is LXE;

[0236] The manufacturer of polyoxyethylene ether is Dow Chemical, and the product model is TERGITOL TM 15-S-7;

[0237] The alcohol polyether surfactant is specifically polyoxyethylene (20) octylphenol, which is produced by Zibo Zhongcheng and the product model is OP-20.

[0238] Comparative Example 4 (Epoxy Resin System Adhesive)

[0239] The raw materials of this comparative example are calculated by mass:

[0240] The epoxy resin is 15 parts, the manufacturer is Baling Petrochemical, and the product model is CYD-128 (E-51);

[0241] The number of parts of amine curing agent is 5 parts;

[0242] The number of parts of kaolin powder in Example 2 is 12 parts;

[0243] The number of parts of talcum powder is 6 parts;

[0244] The number of parts of titanium oxide is 3 parts;

[0245] The number of parts of modified starch is 6 parts;

[0246] The number of parts of thickener (HPMC) is 3 parts;

[0247] The number of parts of cross-linking agent (melamine) is 2 parts;

[0248] pH regulator (sodium acetate) is 0.3;

[0249] The surfactant (polyoxyethylene (20) octylphenol) was present in an amount of 0.8 parts;

[0250] Water is 60 parts.

[0251] Comparative Example 5 (acrylic acid system adhesive)

[0252] The raw materials of this comparative example are calculated by mass:

[0253] Acrylic resin is 18 parts, the manufacturer is BASF, the product model is A 81;

[0254] The kaolin powder in Example 2 is 14 parts;

[0255] 5 parts of talcum powder;

[0256] 3 parts of titanium oxide;

[0257] Modified starch is 7 parts;

[0258] Thickener (HPMC) is 3 parts;

[0259] Cross-linking agent (melamine) is 2 parts;

[0260] PH regulator (sodium acetate) is 0.4 parts;

[0261] Surfactant (polyoxyethylene (20) octylphenol) is 1 part;

[0262] The amount of water is 65 parts.

[0263] Comparative Example 6 (starch adhesive)

[0264] Modified starch is 25 parts;

[0265] Thickener (HPMC) is 5 parts;

[0266] PH regulator (sodium acetate) is 0.3 parts;

[0267] Surfactant (polyoxyethylene (20) octylphenol) 0.7 parts;

[0268] Preservative (phenoxyethanol) is 0.5 parts;

[0269] Water is 60 parts.

[0270] Comparative Example 7 (polyvinyl acetate (PVA) system adhesive)

[0271] Polyvinyl acetate (PVA) is 20 parts, the manufacturer is Japan Kuraray, the product model is 224;

[0272] Thickener (HPMC) is 3 parts;

[0273] PH regulator (sodium acetate) is 0.5 parts;

[0274] Surfactant (polyoxyethylene (20) octylphenol) 0.8 parts;

[0275] Preservative (phenoxyethanol) is 0.5 parts;

[0276] Water is 70 parts.

[0277] Performance Testing

[0278] Performance testing: Performance tests include tensile strength, shear strength, peel strength, whiteness, static delamination, storage stability, viscosity, drying speed and water resistance.

[0279] This application conducted a comparative test on the performance of Examples 4 to 13 and Comparative Examples 1 to 7, and the test method is as follows:

[0280] 1. Test for tensile strength

[0281] Test standard: ISO527 Plastic Tensile Properties Test, tensile strength is used to evaluate the adhesive's ability to resist fracture under tensile load.

[0282] Equipment: Universal material testing machine. This test uses an Instron testing machine.

[0283] Test steps:

[0284] Apply the adhesive to a standard cardboard or film sample and wait for it to dry completely. Use a shear knife to cut the sample into the specified size (e.g., 50mm x 25mm). Place the sample in a universal material testing machine and test the maximum load at which the sample breaks under tensile load. Calculate the tensile strength: Tensile strength = maximum load / sample cross-sectional area.

[0285] 2. Shear strength test

[0286] Test standard: ISO 4587 Adhesives - Tensile shear strength test. Shear strength is used to evaluate the adhesive's ability to withstand shear loads.

[0287] Equipment: Universal material testing machine. This test uses an Instron testing machine.

[0288] Test steps:

[0289] Apply adhesive to the contact surface of paper and wait for it to dry completely. Fix the sample in a testing machine and apply a shear force perpendicular to the contact surface. Measure the maximum load when the adhesive tears and calculate the shear strength: shear strength = shear force / contact area.

[0290] 3. Peel strength test

[0291] Test standard: ISO 11339 Adhesives. T-peel test for flexible to flexible adhesive assemblies. Peel strength is the resistance of the adhesive to separation from the surface.

[0292] Equipment: Peel tester. This test uses a 180° peel tester.

[0293] Test steps:

[0294] Apply the adhesive to paper products or other surfaces, wait until it is completely dry, apply a standard peel angle (such as 180°), separate the adhesive layer from the substrate, record the force required for separation, and calculate the peel strength: Peel strength = applied force / peel width.

[0295] 4. Whiteness test

[0296] Test standard: ISO 2470 Paper, board and pulp. Measurement of blue diffuse reflectance. Whiteness is used to measure the color brightness of the adhesive, focusing on the appearance of the adhesive layer.

[0297] Equipment: Colorimeter or spectrophotometer.

[0298] Test steps:

[0299] Apply the adhesive on standard white paper or coated substrate, wait until it is completely dry, and use a spectrophotometer to measure the reflectance spectrum of the sample to calculate the whiteness index.

[0300] 5. Static stratification

[0301] Test method: Observe with the naked eye whether the adhesive will delaminate or precipitate under static storage conditions.

[0302] Apparatus: This test uses a laboratory cuvette.

[0303] Test steps:

[0304] Place the adhesive sample in a transparent container and observe it standing at room temperature for 1 month to check whether the sample has stratification or precipitation. If the sample has no obvious stratification, it means that the static stability is good.

[0305] 6. Storage stability test

[0306] Test standard: Test the stability of the adhesive within a certain period of time (such as 3 months, 6 months, etc.).

[0307] Equipment: Stability test room. This test uses a standard temperature and humidity chamber.

[0308] Test steps: Place the adhesive sample under the specified storage conditions (e.g., 25°C ± 2°C, 50% relative humidity), take samples at different time points (e.g., 1 month, 3 months, 6 months, etc.) and test its bonding performance. Compare the tensile strength, shear strength and other properties at different time points to evaluate its stability.

[0309] 7. Viscosity

[0310] Test standard: ISO 2555 Viscosity test method. Viscosity test is used to evaluate the fluidity of adhesives and is an important indicator of glue application performance.

[0311] Equipment: Rotational viscometer. This test uses a Brookfield viscometer.

[0312] Test steps:

[0313] Place the adhesive sample in the viscometer container and measure the viscosity of the sample at a specified speed. Use the measured values ​​at different speeds to confirm the viscosity range of the adhesive.

[0314] 8. Drying speed

[0315] Equipment: Timer, oven, or humidity controller.

[0316] Test steps:

[0317] Apply the adhesive to a standard substrate and dry it at room temperature or under heating conditions. Use a timer to record the time required for the coated surface to dry completely until there is no stickiness or moisture.

[0318] 9. Water resistance

[0319] Test standard: BG / T 27328-2011 "Test method for water resistance of organic adhesives", tests the bonding performance of adhesives in wet or water-immersed states.

[0320] Equipment: Immersion tank, universal testing machine. This test uses a common laboratory immersion tank and Instron testing machine.

[0321] Test steps:

[0322] Apply the adhesive to paper or other substrates, wait for it to completely dry, and then completely immerse the prepared adhesive specimen in clean water at room temperature. To simulate water resistance in different environments, different immersion times can be selected, such as 24 hours, 48 ​​hours, 72 hours, etc. At the same time, ensure that the immersion conditions are the same for all specimens. After the predetermined immersion time, remove the specimen from the water and gently wipe the surface moisture with a clean cloth. Then, observe the specimen surface for blistering, peeling, discoloration, etc., and record any changes in the specimen's appearance. Test the adhesive's tensile strength, shear strength, and peel strength to evaluate its water resistance.

[0323] Table 5: Performance test results of Examples 4 to 13 and Comparative Examples 1 to 7

[0324]

[0325] As a thermoplastic elastomer, SBS's unique molecular structure (alternating blocks of styrene and butadiene) imparts strong adhesion properties. When used in adhesives, SBS effectively enhances its bond with paper fibers. The strength of paper products, particularly shear and tensile strength, often relies on the adhesion between the glue and the paper fibers. As a bonding material, SBS can penetrate into the interstices of paper fibers, forming a strong bond, thereby enhancing the overall strength of the paper.

[0326] Polyvinyl alcohol (PVA), polyurethane, and styrene-butadiene-styrene block copolymer (SBS) have the following advantages when used in adhesives: 1. PVA can provide good initial adhesion for the glue, but it itself may be insufficient in terms of strength and durability. As an elastomeric material, SBS can provide good flexibility and durability for the glue, while improving the glue's crack resistance; 2. Polyurethane itself has high strength and good weather resistance. When paired with SBS, the flexibility provided by SBS can complement the strength of polyurethane. SBS makes the glue softer, while polyurethane enhances its mechanical strength and wear resistance, thereby improving the overall performance of the glue; 3. After PVA is combined with polyurethane, the water solubility of PVA can help the glue quickly adhere to the paper surface during the coating process, while the elasticity and durability of polyurethane can enhance the strength and aging resistance of the glue;

[0327] The kaolin powder provided in the present application has the following advantages when used in adhesives: 1. Kaolin itself has excellent whiteness, which can increase the whiteness of the adhesive and make the appearance of the paper products after bonding cleaner and more beautiful; 2. The fine particles and uniform distribution of the kaolin powder help to improve the overall flexural strength of the adhesive, especially interacting to a certain extent with the molecular structures of PVA and SBS, improving the bonding properties of the glue. When used in adhesives for bonding structures such as thin cardboard and paper tubes, the uniform distribution of kaolin can improve the final bonding effect during the bonding process of paper products, effectively increase the mechanical strength of the paper products, such as tensile strength and flexural resistance, and avoid damage caused by external forces; 3. The high whiteness and fine structure of the kaolin powder enable it to be evenly distributed in the adhesive, reducing stratification and precipitation, thereby improving the bonding strength between layers and avoiding stratification and unevenness during the application of the glue;

[0328] Combining the above principle characteristics and performance test results, we can know that:

[0329] The adhesive provided in this embodiment has good tensile strength because the combination of polyvinyl alcohol (PVA), polyurethane (PU) and SBS helps to provide mechanical strength after the adhesive product is formed;

[0330] The good shear strength is due to the use of the kaolin powder prepared in this application and the styrene-butadiene-styrene block copolymer, which together have a reinforcing effect, enhance the internal bonding force of the glue and make the shear strength more stable;

[0331] The peel strength is good because the composite effect of PVA, SBS and kaolin can improve its surface adhesion. Thickeners such as HPMC can also improve adhesion. Good peel strength also contributes to the durability of paper products.

[0332] The high viscosity is not only due to the bonding effect between polyvinyl alcohol (PVA), polyurethane (PU) and SBS, but also due to the use of kaolin powder. The moderate viscosity of kaolin powder makes it have good mechanical properties when used in adhesives.

[0333] The whiteness is above 85%, which is because the addition of kaolin powder and talc generally improves the whiteness of the glue. In addition, the addition of titanium oxide can further enhance the whiteness, especially the kaolin powder produced by the present application. The selection of raw material ore further improves the whiteness. The adhesive with good whiteness is suitable for paper products with high transparency.

[0334] There was no delamination in Examples 4-13. This was partly because the mesh size range of the kaolin powder was suitable and the viscosity was high, and partly because the surfactant improved the dispersibility of the kaolin, thereby effectively preventing delamination.

[0335] The storage stability can be preserved for more than half a year, not only because of the use of preservatives, but also because the fine structure of kaolin powder raw materials ensures no stratification and no deterioration, further improving storage stability;

[0336] At the same time, the drying speed of this application is also relatively fast, and the water resistance is up to 10-14 hours, which is especially suitable for paper products. The good water resistance is not only due to the influence of the cross-linking agent, but the combined effect of polyurethane and SBS also further improves the water resistance.

[0337] In Comparative Example 1, ordinary kaolin was used to prepare the adhesive, and the performance parameters were not as good as those of Examples 4-13, indicating that the kaolin powder provided by the present application has the advantages of high whiteness, moderate viscosity, and high strength.

[0338] Compared with the examples, the tensile strength, shear strength, and peel strength of comparative examples 2-3 were all poor, and delamination occurred, indicating that the ratio provided in this application was within the optimal range.

[0339] Comparative Examples 4-7 used different types of resins to prepare adhesives. After comparison, it was found that the adhesive provided by this application had better performance, especially tensile strength, shear strength, peel strength, whiteness and no stratification phenomenon. It is particularly suitable for paper products, and is preferably used for paper tube adhesives.

[0340] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0341] In this application, the chemical composition and ratio of the kaolin raw materials (including the first kaolin, the second kaolin and the third kaolin) are strictly controlled to ensure that the Al2O3 content exceeds 32%, the LOI (Loss On Ignition) is ≥12%, and other key indicators such as the 325 mesh sieve residue, pH value, viscosity and sedimentation rate are within the optimal range, which is directly reflected in the high whiteness and excellent dispersibility of the kaolin micropowder.

[0342] The introduction of three key steps, namely crushing, grinding (using vertical mill) and homogenization (using Roots blower technology), effectively improves the uniformity, fineness and dispersibility of the micropowder, avoids the powder agglomeration and stratification that may be caused by traditional methods, and thus improves the stability of the micropowder in the adhesive.

[0343] In the adhesive formula of the present application, the synergistic effect of PVA, PU, ​​SBS and components such as kaolin powder, talc, and titanium oxide significantly improves the tensile strength, shear strength, and peel strength of the adhesive. At the same time, due to the addition of kaolin powder and titanium oxide, the whiteness is also greatly improved, meeting the high requirements of high-end paper products for the color transparency of the adhesive.

[0344] The adhesive of the present application is particularly suitable for the field of paper products, especially the production of paper tubes, paper barrels and paper cans. Its excellent performance (such as high tensile strength, shear strength, peel strength and whiteness, as well as good drying speed and water resistance) ensures high-quality output of paper products and meets the production efficiency and strength requirements of high-speed coating machines.

[0345] Compared with the existing technology, this application optimizes the preparation of kaolin powder and the formulation of adhesives, and specifically solves the shortcomings of traditional adhesives in viscosity, whiteness, delamination and water resistance, thereby significantly improving the application performance of adhesives in the paper products industry.

[0346] Techniques, methods, and apparatus known to persons of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, such techniques, methods, and apparatus should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0347] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0348] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A kaolin powder, characterized in that: The kaolin powder contains the following raw material components: a first kaolin having a whiteness of 75% to 80%; second kaolin, wherein the whiteness of the second kaolin is 85% to 90%; third kaolin, wherein the whiteness of the third kaolin is 80% to 90%; Among them, the weight ratio of the first kaolin, the second kaolin and the third kaolin is 1:3:3 to 3:8:7, and the parameters of the kaolin fine powder are: Al2O3 content greater than 32%, 325 mesh sieve residue less than or equal to 1.0%, pH value less than or equal to 8.0, LOI greater than or equal to 12%, and viscosity greater than or equal to 1000 Pa.s.

2. The kaolin powder according to claim 1, characterized in that Measured in weight percentage, the components of the first kaolin include: the components of the first kaolin include: SiO2 40% to 44%, Al2O3 35% to 39%, Fe2O3 0.5% to 0.6%, TiO2 0.5% to 1.5%, K2O≤0.50%, Na2O≤0.20%, SO3≤0.20%, water≤1.0%, and the balance is loss on ignition and trace elements. The COD value of the first kaolin is 8000ppm to 12000ppm.

3. The kaolin powder according to claim 1, characterized in that Measured in weight percentage, the components of the second kaolin include: SiO2 42% to 46%, Al2O3 34% to 38%, Fe2O3 0.5% to 0.6%, TiO2 0.5% to 1.0%, K2O≤0.50%, Na2O≤0.20%, SO3≤0.20%, water≤1.0%, and the balance is loss on ignition and trace elements. The COD value of the second kaolin is 3000ppm to 6000ppm.

4. The kaolin powder according to claim 1, characterized in that Measured in weight percentage, the components of the third kaolin include: SiO2 44% to 48%, Al2O3 33% to 37%, Fe2O3 0.4% to 0.5%, TiO2 0.5% to 1.0%, K2O≤0.40%, Na2O≤0.20%, SO3≤0.20%, water≤1.0%, and the balance is loss on ignition and trace elements. The COD value of the third kaolin is 500ppm to 2000ppm.

5. An adhesive composition, characterized in that In parts by weight, the adhesive comprises: 10-20 parts of polyvinyl alcohol; 5-10 parts of polyurethane; 5 to 10 parts of styrene-butadiene-styrene block copolymer; 10-15 parts of kaolin powder; 5-10 parts of talcum powder; 3-5 parts of titanium oxide; 5-10 parts of modified starch; 0.5-5 parts of thickener; 1 to 3 parts of a cross-linking agent; 0.5-1 part of preservative; 0.2-0.5 parts of pH regulator; 0.5-1 part of surfactant; 70-90 parts water; Wherein, the kaolin powder is the kaolin powder according to any one of claims 1 to 4.

6. The adhesive composition according to claim 5, characterized in that In parts by weight, the adhesive comprises: 13-18 parts of polyvinyl alcohol; 6-7 parts of polyurethane; 5 to 9 parts of styrene-butadiene-styrene block copolymer; 10-15 parts of kaolin powder; 8-10 parts of talcum powder; 3-4 parts of titanium oxide; 8-9 parts of modified starch; 2 to 4 parts thickener; 1 to 3 parts of a cross-linking agent; 0.5-0.9 parts of preservatives; 0.2-0.5 parts of pH regulator; 0.5-0.8 parts of surfactant; 70-72 parts of water, Wherein, the kaolin powder is the kaolin powder according to any one of claims 1 to 4.

7. The adhesive composition according to claim 5 or 6, characterized in that The thickener is one or more of hydroxypropyl methylcellulose, hydroxyethyl cellulose, carbomer, and xanthan gum.

8. The adhesive composition according to claim 5 or 6, characterized in that The preservative is one or more of phenoxyethanol, methylisothiazolinone, and methylchloroisothiazolinone; and / or, The pH regulator is sodium acetate and / or ammonia water.

9. The adhesive composition according to claim 5 or 6, characterized in that: The surfactant is one or more of a polyoxyethylene surfactant and an alcohol polyether surfactant.

10. The adhesive composition according to claim 5 or 6, characterized in that: The cross-linking agent is one or more of melamine and polyhydroxy cross-linking agents.

11. A method for preparing the adhesive composition according to any one of claims 5 to 10, characterized in that: The steps include: S1: adding 20 to 25 parts of water to polyvinyl alcohol and mixing to dissolve and disperse, and adding 10 to 15 parts of water to polyurethane and mixing to dissolve and disperse, respectively preparing a polyvinyl alcohol solution and a polyurethane solution, and mixing the two uniformly; S2: mixing styrene-butadiene-styrene block copolymer with 10-15 parts of water to dissolve and disperse the copolymer, and adding the copolymer to the solution obtained in step S1, and mixing and stirring the mixture until uniform; S3: Mix kaolin powder and talc with 15-20 parts of water to dissolve and disperse them, then add them to the solution obtained in step S2, and then add titanium oxide and mix and stir evenly; S4: Mix the modified starch, cross-linking agent, and thickener with 10 to 15 parts of water for dispersion, add the mixture to the solution obtained in step S3, and then add the preservative and mix well; S5: adding a pH regulator to the solution obtained in step S4 and adjusting the pH value to 4.5-6.5, then adding a surfactant and mixing and stirring uniformly, and then filtering to obtain an adhesive composition product.

12. Use of the adhesive composition according to any one of claims 5 to 10 in the field of paper product adhesives.